Simulation of Transient Flows in Irrigation Canals: Automatic AMIL Radial Gates - Rijo, Manuel (1991)
The computer model SIMCAR for simulation of upstream controlled canal systems was developed. The model solves the gradually unsteady flow in a branched canal network, regarding the singularities: AMIL radial gates, siphons, transitions and confluences. The model is based on the Saint-Venant systems of equations, which are solved by a four-point linear finite-difference implicit scheme weighted in time and space. The final linear system of equations is solved by the double-sweep algorithm. A numerical approach for submerged and free discharge at the gates are presented